Challenges of public and/or private enforcement of the Corporate Governance code - Mohd. Sulaiman, Aiman @ Nariman (Sweet & Maxwell, 2007)
In the realm of corporate and securities regulation, over-regulation has been canvassed as one of the challenges to entrepreneurship. The introduction of Codes is seen as a compromise allowing companies the flexibility to tailor some of its corporate governance processes to its own needs. However, the use of the Code as a corporate governance tool has brought up concerns about the Code’s value in terms of its enforceability. This article focused on how the Code is enforced by the regulators and mechanism in place to ensure public enforcement of the Code,highlighting factors that may impede public enforcement. The article also discusses to what extent is there private enforcement of the Code and the avenues available for private enforcement and the obstacles faced by shareholders' activism.